Efficacy of Newer Molecules, Bioagents and Botanicals against Maydis Leaf Blight and Banded Leaf and Sheath Blight of Maize - Malik, Vinod Kumar (Plant Pathol J, 2018)
Maize (Zea mays L.; 2N=20) is major staple food crop grown worldwide adapted to several biotic and abiotic stresses. Maydis leaf blight (MLB) and banded leaf and sheath blight (BLSB) are serious foliar fungal diseases may cause up to 40% and 100% grain yield loss, respectively. The present studies were undertaken to work out the efficacy of chemicals, botanicals and bioagents for the management of MLB and BLSB under field condition for two seasons Kharif 2014 and 2015. Five molecules (propiconazole 25 EC, hexaconazole 25 EC, carbendazim 50 WP, mancozeb 75 WP and carbedazim 12 WP + mancozeb 63 WP), two bioagents i.e. Trichoderma harzianum and T. viridae and three botanicals namely azadirachtin, sarpagandha and bel pathar were tested for their efficacy against MLB. Eight newer fungicides viz., difenconazole 250 SC, hexaconazole 5 EC, carbendazim 50WP, validamycin 3 L, tebuconazole 250 EC, trifloxystrobin 50 WG + tebuconazole 50 WG, azoxystrobin 250 EC and pencycuron 250 SC were evaluated against BLSB. Analysis revealed significant effects of propiconazole at 0.1%, carbendazim 12 WP + mancozeb 63 WP at 0.125% and sarpagandha leaves at 10% against MLB pathogen, whereas validamycin at 0.1% and trifloxystrobin 25 WG + tebuconazole 50 WG at 0.05% were found effective against BLSB. The slow rate of disease control virtually by the bioagents might have not shown instant effect on plant response to the yield enhancing components. The identified sources of management can be used further in strengthening the plant protection in maize against MLB and BLSB.